Calculation of ankle and knee joint moments during ACL-injury situations in soccer - Grund, T.; Reihl, I.; Krosshaug, T.; Senner, V.; Gruber, K. (Procedia Engineering, 2010)
The basis of ACL-injury prevention is the understanding of the injury mechanism. Therefore a new approach was developed and validated that enables the calculation of knee and ankle joint moments during the injury. Detailed analysis of ACL-injury situations was performed to detect the kinematics as input data for a simplified 3D-human body model. An inverse-dynamics approach was used to realize the movement. The model was driven by Net-Muscle-Torque-Motors that calculate 3-D ankle and knee joint moments. Although there are some limitations that have to be considered this approach has the potential to generate a better understanding of injury mechanisms.